Social class and the fertility transition: A critical comment on the statistical results reported in Simon Szreter's fertility, class and gender in Britain, 1986-1940 - Geoffrey Barnes; Timothy W. Guinnane (Yale University, Economic Growth Center, 2010)
Simon Szreter's book Fertility, Class, and Gender in Britain, 1860-1940 argues that social and economic class fails to explain the cross-sectional differences in marital fertility asreported in the 1911 census of England and Wales. Szreter's conclusion made the book immediately influential, and it remains so. This finding matters a great deal for debates about the causes of the European fertility decline of the nineteenth and twentieth centuries. For decades scholars have argued whether the main forces at work were ideational or social and economic. This note reports a simple re-analysis of Szreter's own data, which suggests that social class does explain cross-sectional differences in English marital fertility in 1911.
Keywords: J13; N33; 330; Fertility transition; 1911 Census of England and Wales